2021
DOI: 10.3389/fpls.2021.616645
|View full text |Cite|
|
Sign up to set email alerts
|

Microplastic Shape, Polymer Type, and Concentration Affect Soil Properties and Plant Biomass

Abstract: Microplastics may enter the soil in a wide range of shapes and polymers. However, little is known about the effects that microplastics of different shapes, polymers, and concentration may have on soil properties and plant performance. To address this, we selected 12 microplastics representing different shapes (fibers, films, foams, and fragments) and polymers, and mixed them each with soil at a concentration of 0.1, 0.2, 0.3, and 0.4%. A phytometer (Daucus carota) grew in each pot during 4 weeks. Shoot, root m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
133
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 351 publications
(145 citation statements)
references
References 58 publications
(43 reference statements)
9
133
3
Order By: Relevance
“…Our results indicated that microplastic foams and fragments increased soil pH, which can be due to the increase in soil aeration and porosity when these microplastics were added into the soil (de Souza Machado et al, 2019;Lozano et al, 2021a). This along with the leaching of microplastic chemical compounds into the soil (Kim et al, 2020;Waldman and Rillig 2020), may alter soil biota with consequences for soil pH.…”
Section: Microplastics Increased Soil Phmentioning
confidence: 74%
See 3 more Smart Citations
“…Our results indicated that microplastic foams and fragments increased soil pH, which can be due to the increase in soil aeration and porosity when these microplastics were added into the soil (de Souza Machado et al, 2019;Lozano et al, 2021a). This along with the leaching of microplastic chemical compounds into the soil (Kim et al, 2020;Waldman and Rillig 2020), may alter soil biota with consequences for soil pH.…”
Section: Microplastics Increased Soil Phmentioning
confidence: 74%
“…This may could be the reason that PE foams caused higher respiration that PE films. Films and fragments had neutral effects on soil respiration, while positive effects have been observed on this property when a plant species was included in the system (Lozano et al, 2021a). The latter as the presence of roots in the soil matrix contributes to soil aggregation and facilitates water uptake and its redistribution through the soil profile, which in the end promote soil microbial activity (Lozano et al, 2021a).…”
Section: Microplastics Affect Soil Respiration After Long Incubation Timementioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that the commercial microspheres used in this study are indeed inert and their ingestion may not substantially reduce the protist's food intake. More research using different soils and a wider diversity of MPs types (e.g., varying the parameters shape (Lozano et al, 2021), polymer type , weathering status and additives ) will be required to clarify this.…”
Section: Discussionmentioning
confidence: 99%